Integrating Local History and Landscape Archaeology: two case studies from western Greece - Simoni, Helene; Papagiannopoulos, Kostas (Journal of Greek Archaeology, 2017)
Local History examines the history of a relatively small geographical area, the boundaries of which are based on particular characteristics of its landscape, natural and/or cultural, and is mostly practised by amateur historians who intend to write a book about their place of origin or residence without being committed to following strict research standards and rules. On the other hand, Landscape Archaeology is an academic discipline that is defined as the archaeological study of the relationship of people with their environment in the Past, as well as the relationships between people within the environmental context which they inhabited. Even though the academic framework in which landscape archaeologists operate provides more reliable and better documented results, their work seems to lack the vigour that closer communication with locals and a deeper understanding of the hidden perceptions of a community can provide.